Simultaneous use of plant growth promoting rhizobacterium and nitrogenous fertilizers may help in promoting growth, yield, and nutritional quality of okra. (28th May 2017) - Nazir, Qudsia; Akhtar, Muhammad Javed; Imran, Muhammad; Arshad, Muhammad; Hussain, Azhar; Mahmood, Sajid; Hussain, Sabir
ABSTRACT: This study was conducted to evaluate the simultaneous use of plant growth promoting rhizobacterium (QS1) and different combinations of urea-nitrogen and biogas slurry-nitrogen for improving growth, yield, and nutritional quality of field grown okra. The isolate QS1 was identified as Bacillus sp. QS1 based on its ribosomal ribonucleic acid (rRNA) sequence analysis. Results revealed that among the combinations, the application of 50% urea-nitrogen + 50% biogas slurry-nitrogen was optimal for improving crop performance. This combination significantly (p ≤ 0.05) promoted okra growth viz. plant height (69.63–80.03 cm), no of branches per plant (14–18), shoot fresh weight (86.66–136.25 g/plant), root fresh weight (22.5–26.58 g/plant), and fruit yield (8.5–13.5 kg/plot) compared to the plants receiving 100% urea-nitrogen. The interactive effective of this nitrogen combination and QS1 inoculation produced the highest growth and yield response. Similarly, the same treatment improved nitrogen, phosphorus, potassium, and protein contents in shoot and fruit of okra compared to other treatments.